Seasonal and interannual behaviour of groundwater catchment boundaries in a Chalk aquifer. Issue 1 (21st July 2015) - Parker, Simon J.; Butler, Adrian P.; Jackson, Christopher R.
Abstract: Groundwater catchment boundaries and their associated groundwater catchment areas are typically assumed to be fixed on a seasonal basis. We investigated whether this was true for a highly permeable carbonate aquifer in England, the Berkshire and Marlborough Downs Chalk aquifer, using both borehole hydrograph data and a physics‐based distributed regional groundwater model. Borehole hydrograph data time series were used to construct a monthly interpolated water table surface, from which was then derived a monthly groundwater catchment boundary. Results from field data showed that the mean annual variation in groundwater catchment area was about 20% of the mean groundwater catchment area, but interannual variation can be very large, with the largest estimated catchment size being approximately 80% greater than the smallest. The flow in the river was also dependent on the groundwater catchment area. Model results corroborated those based on field data. These findings have significant implications for issues such as definition of source protection zones, recharge estimates based on water balance calculations and integrated conceptual modelling of surface water and groundwater systems. Copyright © 2015 John Wiley & Sons, Ltd.